Empowering Marginalized Children Through Educational Board Games: A Community-Based Approach to Literacy and Numeracy Development - Sandjaja, Meilani; Yuliawati, Livia; Eunike, Prisca; Ega Vishnu Christian, Yohanes; Shienny Davanca Lisvantoro, Stephanie; Priska Christian, Jennifer; Aishvarya Divani, Shri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Foundational literacy and numeracy remain major educational challenges among marginalized children in Indonesia, particularly those from street-connected and low-income communities who have limited access to engaging learning resources and structured educational support. This community service project aimed to evaluate the effectiveness of the Kicara Board Game (